"Another tool in our toolbox": a scoping review of the use of eHealth technologies in health social work practice. (2nd January 2023) - Tickner, Campbell; Heinsch, Milena; Brosnan, Caragh; Kay-Lambkin, Frances
ABSTRACT: There is increasing recognition of the salience of eHealth technologies in enhancing health service capacity. Yet social work remains "behind the curve" in progressing digital practices. As the demand for digital health care increases, particularly following COVID-19, it is becoming increasingly urgent to understand how social workers engage with eHealth technologies, and how technological engagement impacts on social work practice. In this scoping review, we sought to examine eHealth use in health social work practice. Our findings suggest that, while social workers recognize the strengths and opportunities to broaden the scope of their practice, they remain concerned that eHealth may not be congruent with the values and approaches of the profession. This review provides a broad overview of health social workers' engagement with eHealth technologies and considers implications for future research that examines the nuanced and complex nature of professional values, risk, and assessment in the digital space.